An adaptive supply chain cyber risk management methodology - Stefan Schauer; Martin Stamer; Claudia Bosse; Michalis Pavlidis; Haralambos Mouratidis; Sandra König; Spyros Papastergiou (Digitalization in Supply Chain Management and Logistics: Smart and Digital Solutions for an Industry 4.0 Environment. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 23, 2017)
Maritime information infrastructures have developed to highly interrelated cyber ecosystems, where ports as well as their partners are connected in dynamic Information and Communication Technology (ICT)-based maritime supply chains. This makes them open and vulnerable to the rapidly changing ICT threat landscape. Hence, attacks on a seemingly isolated system of one business partner may propagate through the whole supply chain, causing cascading effects and resulting in large-scale impacts. In this article, we want to present a novel risk management methodology to assess the risk level of an entire maritime supply chain. This methodology builds upon publicly available information, well-defined mathematical approaches and best practices to automatically identify and assess vulnerabilities and potential threats of the involved cyber assets. This leads to a constantly updated risk evaluation of each business partner's cyber assets together with their cyber interconnections with other business partners. The presented risk management methodology is based on qualitative risk scales, which makes the assessment as well as the results more intuitive. Furthermore, it enables a holistic view on all of the integrated ICT-systems as well as their interdependencies and thus can increase the security level of both a whole supply chain and every participating business partner.
urn:nbn:de:gbv:830-88217359; 10419/209192; https://econpapers.repec.org/RePEc:zbw:hiclpr:23
Keywords: 650; IT security; cyber risk management; cyber risk assessment; maritime supply chains